Analisis Perbandingan Statistik Deskriptif Nilai Ujian Mahasiswa Menggunakan Matlab - Maudi Chindi Pratiwi; Muhammad Rouf; Bento Saputra; Muhammad Nur Hadi (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze and compare the results of the Engineering Mathematics course exam between class A and class B in the Electrical Engineering Vocational Education Department. A comparative analysis of exam scores is necessary to identify differences in student academic achievement and to serve as a basis for efforts to improve the quality of the learning process. The research method used is descriptive statistics with a quantitative approach. The research procedure includes compiling frequency distribution tables based on score categories, creating graphs from frequency distribution data, and calculating measures of central tendency and dispersion of data. The research data consisted of exam scores from 71 students divided into two classes, namely 36 students in class A and 35 students in class B. All calculations were performed using MATLAB software and validated through manual calculations to ensure the accuracy of the results. The results showed that the average scores of both classes were relatively the same, but class A had a greater variation in scores than class B. This indicates that the academic achievement of students in class B was more evenly distributed. The presentation of the results in the form of histograms and pie charts facilitated the interpretation of the characteristics of the score distribution in each class.